ANALISIS JURIDIS KEDUDUKAN PERJANJIAN KEMITRAAN ANTARA PENGEMUDI JASA ANGKUTAN ONLINE DAN PERUSAHAAN PROVIDER DITINJAU DARI ASPEK HUKUM KEPERDATAAN - Zuhriati Khalid (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The legal position between the drivers of online transportation services and the online transportation application service company is a partnership agreement as regulated in civil law. However, in practice the existing legal regulations have not provided legal protection to drivers of online transportation because not all drivers of online transportation understand their position as a partnership relationship. If it is associated with civil law, this is contrary to the principle of balance; it can even be said to be an abuse of the situation (misbruik van omstadigheden). The misuse of this situation can occur if an agreement is born due to economic excellence, psychological superiority and other advantages. The purpose of this study is to see how existing legal regulations actually runs effectively and efficiently in the community. The method of this research is qualitative research, namely based on the principles of law, doctrine and legislation that can answer the problems of this study. Keywords : Partnership Agreement, Driver, Online Transportation